Anticoagulant properties of a high molecular weight polysaccharide fraction (1000RS) of the ascidian Microcosmus exasperatus - Restrepo-Espinosa, Diana C.; Motta, Juliana María; Teixeira, Felipe Castro O. de B.; Román, Yony; Colorado-Ríos, Jhonny; Pavão, Mauro S. G.; Martínez, Alejandro (Ars Pharmaceutica (Internet), 2017)
Aims: The anticoagulant effect and cytotoxicity of a high molecular weight polysaccharide fraction (1000RS) obtained from the tunic of the ascidia Microcosmus exasperatus were evaluated. Methods: Anticoagulant properties of 1000RS was evaluated by activated Partial Thromboplastin Time (aPTT), Thrombin Time (TT), Prothrombin Time (PT), anti-factor Xa and lupic anticoagulant (dRVVT) assays. Cytotoxicity was tested on murine hematopoietic cells using MTT assay. Results: This galactose rich fraction showed to be a potential anticoagulant due to its inhibitory effect on the intrinsic coagulation pathway. At the same time, anticoagulant doses of this fraction have no effect on cellular viability, which means that it can be used as a therapeutic agent. Conclusion: In vitro anticoagulant effect of 1000RS occurs at innocuous doses, however, it still need to be tested using in vivo models and its cytotoxicity evaluated in normal human cell lines.